Synthesis of Phosphate Ethanolamide Derived from Free Fatty Acids of Cooking Oil Processing From Crude Palm Oil. (Journal of Chemical Natural Resources, 2021)
Synthesis of Phosphate Ethanolamide Derived from Free Fatty Acids of Cooking Oil Processing From Crude Palm Oil.